EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN PEMBERDAYAAN MASYARAKAT DI INDONESIA WILAYAH NTB - Prasetyo Ishwayudi (Jurnal Penelitian)
Many infrastructure developments in Eastern Indonesia have certainly been carried out, including the expansion of airports, with the hope that it will make air transportation easier and faster. The expansion of the airport certainly requires the availability of human resources in it. . It is necessary to fulfill the need for the availability of resources with certain required criteria. One of the Polytechnics appointed to meet the availability of Human Resources, by empowering the community for the Eastern region, namely NTB, is the Surabaya Aviation Polytechnic (Poltekbang). This study uses a qualitative method. With this Education and Training, you can increase the knowledge, attitudes and skills of Human Resources in Indonesia. Data collection method using; Interviews, Research, Observations, and Documentation. The results of the evaluation based on CIPPO (Context, Input, Process, Product, Outcome) can be concluded that the education and training program has been running well supported by the readiness and quality of teaching staff but still has deficiencies, especially those that occur in NTB where facilities and infrastructure are lacking adequate.